Users' Experience of Digital Wayfinding Screens: A Uses and Gratification Perspective from South Africa. (7th July 2020) - Roux, Thérèse
Abstract : Marketing and business communication researchers have neglected the wayfinding capabilities of digital out-of-home communication in the retailing landscape. The current study focuses on digital wayfinding screens in the South African shopping mall environment. The aim is understanding users' experience of digital wayfinding screens, guided by the uses and gratification theory. Shoppers were interviewed about their views and actions while engaging in the wayfinding process in large upmarket shopping malls. The in-depth semistructured interviews were recorded and then the content was analysed. The findings provide a rich and comprehensive understanding of shoppers' content gratifications and process gratifications when utilising this contemporary medium. The current study identifies four uses and gratifications for digital wayfinding screens: convenient process gratifications, interactive process gratifications, informational content gratification, and entertaining content gratifications. Understanding the gratification dimensions of digital wayfinding screens contributes to contemporary media research and forms the basis of valuable guidelines for practitioners in retail media and design.